Economic burden of cancer among patients with surgical resections of the lung, rectum, liver and uterus: Results from a US hospital database claims analysis - Iftekhar Kalsekar; Chia-Wen Hsiao; Hang Cheng; Sashi Yadalam; Brian Po-Han Chen; Laura Goldstein; Andrew Yoo (Health Economics Review, 2017)
Objectives: To determine hospital resource utilization, associated costs and the risk of complications during hospitalization for four types of surgical resections and to estimate the incremental burden among patients with cancer compared to those without cancer. Methods: Patients (=18 years old) were identified from the Premier Research Database of US hospitals if they had any of the following types of elective surgical resections between 1/2008 and 12/2014: lung lobectomy, lower anterior resection of the rectum (LAR), liver wedge resection, or total hysterectomy. Cancer status was determined based on ICD-9-CM diagnosis codes. Operating room time (ORT), length of stay (LOS), and total hospital costs, as well as frequency of bleeding and infections during hospitalization were evaluated. The impact of cancer status on outcomes (from a hospital perspective) was evaluated using multivariable generalized estimating equation models; analyses were conducted separately for each resection type. Results: Among the identified patients who underwent surgical resection, 23 858 (87.9% with cancer) underwent lung lobectomy, 13 522 (63.8% with cancer) underwent LAR, 2916 (30.0% with cancer) underwent liver wedge resection and 225 075 (11.3% with cancer) underwent total hysterectomy. After adjusting for patient, procedural, and hospital characteristics, mean ORT, LOS, and hospital cost were statistically higher by 3.2%, 8.2%, and 9.2%, respectively for patients with cancer vs. no cancer who underwent lung lobectomy; statistically higher by 6.9%, 9.4%, and 9.6%, respectively for patients with cancer vs. no cancer who underwent LAR; statistically higher by 4.9%, 14.8%, and 15.7%, respectively for patients with cancer vs. no cancer who underwent liver wedge resection; and statistically higher by 16.0%, 27.4%, and 31.3%, respectively for patients with cancer vs. no cancer who underwent total hysterectomy. Among patients who underwent each type of resection, risks for bleeding and infection were generally higher among patients with cancer as compared to those without cancer. Conclusions: In this analysis, we found that patients who underwent lung lobectomy, lower anterior resection of the rectum (LAR), liver wedge resection or total hysterectomy for a cancer indication have significantly increased hospital resource utilization compared to these same surgeries for benign indications.
Keywords: 330; Surgical organ resections; Healthcare costs; Economic burden; Cancer surgery